Digital-Based Internationalization Strategy In Penetrating The Global Market: A Case Study On Footwear MSMes in Mojokerto - Arif Isnaini; Sudarmiatin; Heri Pratikto (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
This research aims to analyze the digital-based internationalization strategy implemented by "Kenzi" Mojokerto footwear MSMEs, as part of creative industry players in the Mojokerto footwear center, which is known to have hundreds of craftsmen with national and international standard product quality. This research uses a qualitative approach with a case study design on "Kenzi" MSMEs that have penetrated foreign markets through digital channels. Data collection techniques were carried out through in-depth interviews, observations, and documentation, with data analysis using interactive models. The results of the study show that the "Kenzi" MSME internationalization strategy is carried out through the optimization of the global marketplace, social media, and strengthening digital branding to increase product visibility in the international market. Competitive advantage lies in product design that is adaptive to global trends, local craftsmanship-based quality, and production flexibility. However, the challenges faced include limited production capacity, suboptimal digital literacy, and the complexity of international export and logistics regulations. This research contributes to the development of a contextual digital-based internationalization strategy model for footwear MSMEs, especially in the Mojokerto area, as the center of the footwear industry, and becomes the basis for policy recommendations in encouraging MSMEs to go global.